Stable Isotope Analysis Revealed Ontogenetic Changes in Trophic Ecology and Migration Patterns of Sepia esculenta in the Northern Coastal Waters of China - Wang, Linlong; Liu, Yang; Zhang, Xiumei (Frontiers in Marine Science, 2022)
Golden cuttlefish Sepia esculenta, the most important cephalopod economically in the northern coastal seas of China, had experienced greatly reduced population biomass due to continuous fishing pressure in recent decades. Understanding the trophic ecology and clarifying the spatial distribution of wintering ground can help develop management plans for this species. In this study, the ontogenetic changes in the trophic ecology of S. esculenta in the Qingdao coastal waters were determined and the migration patterns were studied using stable isotope analysis. Cluster analysis based on isotopic values divided the S. esculenta that has different length into groups 11-20 mm, 21-100 mm, and 121-200 mm. A significant difference in the δ13C values between the groups 11-20 mm (-17.10‰) and 21-100 mm (-15.89‰), illustrating an ontogenetic change in feeding habits. Due to the migratory habits of S. esculenta, the δ13C value of group 121-200 mm (-16.39‰) was lower than that of group 21-100 mm. The δ15N values of S. esculenta were found to increase with length, and there was a clear linear relationship between different S. esculenta groups, suggesting that the wintering ground may locate in the same latitude as the spawning ground (i.e. the middle Yellow Sea). Furthermore, the trophic relationship between the S. esculenta and coexisting species was assessed, revealed group 11-20 mm of S. esculenta has some overlap of carbon isotope space with other species, suggesting that these species may feed on it as prey. Thus, slightly increasing the length to more than 20 mm may reduce the pressure of being prey of post-released juveniles of S. esculenta and improve the effect of release.